2013
DOI: 10.1016/j.conbuildmat.2012.11.115
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening double curved arch bridges by using extrados section augmentation method

Abstract: Double curved arch bridges have played an important role in the history of bridge constructions in China. The strengthening or retrofitting of this type of bridge has attracted a great deal of research attentions in the Chinese bridge engineering community. In this paper, a novel strengthening method, i.e. the extrados section augmentation strengthening method (ESASM), has been reported. Firstly, the rationales of this new method and the resulting changes in internal forces have been studied in details. A nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…2. The high nonlinearity of the structure and the working behavior involving various parameter uncertainties [ 19 ] make CPCBG bridge structures exhibit complex failure mechanisms; the current study of the failure process focuses on the ultimate collapse state [ 4 , 8 , 20 , 21 , 22 , 23 ], but does not give a clear judgment basis to define when the bridge structure starts to lose it. In fact, this conservative approach is aimed at avoiding and reducing the negative effects of inaccurate predictions, which may lead to considerable material costs and even to the irrationality of the structural design due to the negative impact.…”
Section: Introductionmentioning
confidence: 99%
“…2. The high nonlinearity of the structure and the working behavior involving various parameter uncertainties [ 19 ] make CPCBG bridge structures exhibit complex failure mechanisms; the current study of the failure process focuses on the ultimate collapse state [ 4 , 8 , 20 , 21 , 22 , 23 ], but does not give a clear judgment basis to define when the bridge structure starts to lose it. In fact, this conservative approach is aimed at avoiding and reducing the negative effects of inaccurate predictions, which may lead to considerable material costs and even to the irrationality of the structural design due to the negative impact.…”
Section: Introductionmentioning
confidence: 99%
“…Tao et al [2] studied the effect of using FRP as a repair material applied on the intrados of a large model masonry arch bridge of two vents. Juntao Kang et al [5] reported that the internal forces in a double curved arch bridge have been favorably redistributed by adding reinforced concrete layer at specific portions of the extrados surface of the bridge. Anania et al [6], introduced a technique based on the use of the composite CFRP applied using a calibrated shape ''Ω-Wrap'' around a high resistance mortar core realized at the barrel vault extrados as a supporting rib.…”
Section: Introductionmentioning
confidence: 99%